2013
DOI: 10.3912/ojin.vol18no02man03
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Control Over Practice and Teamwork

Abstract: Nurses’ control over practice is essential to nursing care quality and fosters teamwork at the point of care delivery. This article describes a study to measure the impact of nurses’ control over their practice from the perspective of teamwork. The purpose of this study was to measure the relationship of control over practice to the five following dimensions of teamwork: team structure, leadership, situation monitoring, mutual support, and communication. The study method was a secondary analysis of 456 surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Schwendimann et al (2016) found no signifiant relationship between nurse job autonomy and job satisfaction in Swiss nursing homes, and Canadian cancer nurses did not see influencing patient care as a key factor for job satisfaction (Bakker et al, 2010). In contrast, Castner et al (2013) found that nurse percieved control of their work improved perceptions of team effectiveness and concluded that leaders should enable this precursor to job satisfaction and ItS. Based on the significant correlations between autonomy, leadership and teamwork, Poghosyan & Liu's (2016) also conclude that poor leadership relationships will negatively influence nurse autonomy and teamwork.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Schwendimann et al (2016) found no signifiant relationship between nurse job autonomy and job satisfaction in Swiss nursing homes, and Canadian cancer nurses did not see influencing patient care as a key factor for job satisfaction (Bakker et al, 2010). In contrast, Castner et al (2013) found that nurse percieved control of their work improved perceptions of team effectiveness and concluded that leaders should enable this precursor to job satisfaction and ItS. Based on the significant correlations between autonomy, leadership and teamwork, Poghosyan & Liu's (2016) also conclude that poor leadership relationships will negatively influence nurse autonomy and teamwork.…”
Section: Resultsmentioning
confidence: 99%
“…It's influence on nurse ItS can vary and may not be direct. For instance, Castner et al (2013) found no relationship between years of experience or training and nurse percieved autonomy, whilst Bakker et al (2010) found that more experienced nurses expected more autonomy and recognition than novices. Schwendimann et al (2016) found no signifiant relationship between nurse job autonomy and job satisfaction in Swiss nursing homes, and Canadian cancer nurses did not see influencing patient care as a key factor for job satisfaction (Bakker et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Situation monitoring is different from watching teammates doing their work [ 29 ]. Situation monitoring is described as an awareness of the interconnected team performance and functioning and its environment [ 30 ]. Members of the healthcare team, particularly in the critical care unit, need to see the whole situation and how their other members perform to make necessary adjustments and form an effective healthcare team.…”
Section: Discussionmentioning
confidence: 99%